The Chinese Role in the Russian Ukrainian War: international and political journal - Zuwayr, Assistant Prof. Dr. Entedar Rashid (The International and Political Journal, 2025)
China, through its position on the Russian Ukrainian war, tried to avoid many future risks and challenges by calling for dialogue and peace talks to end the crisis, in addition to its recognition of Ukraine’s sovereignty. At the same time, Chinese officials were keen to avoid describing the war as a Russian invasion and rejected broad Western sanctions on Russia. They also acknowledged that Russia’s security demands regarding the security system in Europe are legitimate. Thus, China is keen to deal with all future possibilities of this war and seeks to turn any crisis into an opportunity to invest in achieving its goals.